PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN NKRI MENGGUNAKAN PROBLEM BASED LEARNING DI KELAS V SDN 11 PAUH KOTA PADANG - buulolo, Silvia; Amsari, Dina; Yenti, Yesni; Media, Afriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the problem of low student learning outcomes in Pancasila Education, specifically the Unitary State of the Republic of Indonesia (NKRI), in fifth-grade students at SDN 11 Pauh, Padang City. These low learning outcomes are influenced by the teacher-dominated learning process, suboptimal use of learning tools, and a lack of active student participation during learning activities. This study aims to describe improvements in student learning outcomes through the application of the Problem-Based Learning (PBL) model. The method used was Classroom Action Research (CAR), implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The research subjects consisted of 29 fifth-grade students at SDN 11 Pauh, Padang City. Data collection techniques included observation, learning achievement tests, and documentation. The results showed that the application of the Problem-Based Learning model increased student engagement in learning and positively impacted learning outcomes. Therefore, the PBL model can be an effective alternative learning method for Pancasila Education in elementary schools.